The Future of Autonomous Cars in the Daily Life of Cities: A Systematic Literature Review - Lopes, Gustavo Bernardo; Siqueira, Anderson; Araújo, Eric; Santos, Pedro; Santos, Simone C. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2021)
An autonomous car is a driverless vehicle for the purpose of navigating autonomously and safely over the earth's surface. Interest in this type of transport has increased significantly in recent years and it is possible that the number of these vehicles on the streets will increase, changing the daily lives of cities. In this context, this work aims to understand the technological limitations and impacts of using autonomous cars, observing the feasibility, adaptation, traffic legislation, and perceived benefits. Following the method of systematic literature review proposed by Kitchenham, 69 primary studies from relevant bases in the area of Technology were analyzed. These studies showed some evidence by indicating, for example, that there will be a change in the way people relate to cars, particularly in terms of sharing them, in addition to impacts on urban mobility.